Relation Between Crude Oil and Indonesia Stock Market - Gaol, Yosua Lumban; Faturrohman, Taufik (Journal of Business and Management, 2016)
Abstract. The surge in crude oil price in the course of a recent year has created lots of interest for the relationship between crude oil price and the stock market. In recent year, crude oil price had significant move in the world. Crude oil price decreases to lower price in the history. This situation makes the company get significant impact especially for Energy Company and Production Company that used crude oil for primary material that will affect stock value of the company. The little move in crude oil price will give move in country stock market performance.  That movement makes some impact in the Indonesia stock market that their stock has unpredicted move in the Indonesia stock market. The movement of crude oil price will affect movement stock market get negative or positive impact. It will make investor and internal management make some policy to move in Indonesia stock market based on analysis of the relation between crude oil price and the stock market. The researcher propose of this study to know how far dynamic relation between crude oil price and stock market  in emerging market like Indonesia. This research will give comprehensive study about the relation between oil price and stock market for large scope research. the investor can make this research can be used in make decision making to invest in Indonesia The data about IHSG and stock price will gather from Yahoo Finance and crude oil price will be gather from Bloomberg Website. The range time period of data is from January 2008 to April 2016. The methodology of this study is use unit root test, Johansen’s cointegration test, vector error correction model (VECM), Granger causality test, impulse response functions (IRFs) and variance decompositions (VDCs) to looking relation between crude oil price and Indonesia Stock Market. The result of these studies is there a not relationship between crude oil price and Indonesia Stock market in a long-term relationship. This result will give insight to future research about relation oil price and stock market and give one subject to investor in make decision to invest in Indonesia  Keyword: Crude oil price, Stock Market, Long-term relationship, Indonesia